The impact of motor status on the quality children’s life - Shkodra, Mimoza Moza; Bislimi, Arben (Journal of Education, Health and Sport, 2021)
The basic purpose of this paper is to distinguish between the motor characteristics of students (male-female) and 12-year-old age groups of SHFMU "Selami Hallaci" in Gjilan. The sample of this research includes a total of 100 (50 female and 50 male) students who undergo regular physical education and sports two hours a week. 6 basic motor variables were applied in the research, and based on it, significant differences were obtained. To confirm the differences between students in the basic motor variables, the T-test method was used. Based on the results obtained through this method, valid changes were realized in some of the basic motor variables of. Significant values were obtained in estimating the correlation in some of the motor variables. All these important differences between the mean values in favor of men confirm and confirm that students (men) are more active and agile than the girls tested.